Factors Contributing Towards Slow Adoption of Information Technology (IT): A Literature Review - Nik Fatma Arisya, Nik Yahya; Mazura, Mahdzir; Sharifah Mazlina, Syed Khuzzan (INTI International University, 2019)
Innovation issues have long been regarded as a global concern within worldwide countries including Malaysia. One of the difficulties is regarding the slow organisational innovation within construction organisations in adopting Information Technology (IT). A lot of factors have been discussed in the literature leading towards slow organisational innovation; with respect to slow adoption of IT. Hence, the objectives of this paper are; to critically review the components contributing to slow organisational innovation, i.e. slow adoption of IT, and to synthesize the available literature and tease out the most significant factor causing the slow adoption of IT in planning the way forward. Using frequency analysis of content-based method, four main categories were teased and can be broadly divided into four namely, people, management, technology, and process. Based on the findings, people were identified as the most concerned factor rose by researchers; which include the managerial skills played by owner(s), leader(s), top management team or managerial position within organisation in influencing the technological adoption. A way forward was recommended in order to overcome the problems within ‘people’ in order to help owners/ leaders/ top management team to make decisions in adopting IT innovation through having ‘good’ managerial skills.